MAPPING THE RESEARCH TAX CREDIT ON BIBLIOMTERIC ANALYSIS AND LITERATURE REVIEW - Tri Ananda Rizky; Sri Andriani (Program Studi Akuntansi, Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy Situbondo, 2024)
Tax Credits have served as an important fiscal policy tool in many countries; however, the scientific exploration of this area remains incomplete. The purpose of this study is to examine and map the Tax Credits research domain. Using a dual methodological strategy, this study conducted a bibliometric analysis using VOSViewer and a literature review. VOSViewer bibliometric analysis was used to visually represent the distribution of academic publications and determine key research clusters, while the literature review aimed to highlight dominant research themes. An examination of academic publications revealed the presence of 400 relevant journal articles on Tax Credits, underscoring the noteworthy research interest in this subject. The methodology consisted of: (1) visualization of the distribution of journal publications related to Tax Credits; (2) visualization of VOSViewer bibliometric results related to Tax Credits, focusing on the identification of clusters and their components; and (3) identification of research themes regarding Tax Credits through a review of existing literature. The findings show that: (1) the analysis of journal publications revealed the existence of 400 publications on Tax Credits; (2) the VOSViewer bibliometric analysis illustrated the existence of 5 distinct clusters and 100 topic items in the Tax Credits research network; (3) the literature review highlighted 6 main themes related to the impact of Tax Credits. Tax Credits have emerged as a captivating subject of study with far-reaching consequences. This research lays a solid foundation for future investigations on Tax Credits and facilitates the formulation of more efficacious policies.